Increasing Mastery of English Vocabulary through Think Pair Share Techniques - Zaini Hasan (Sean Institute, 2020)
The researcher shows that the lack of mastery of English vocabulary in semester 1 students of the University of Gunung Leuser needs to be overcome using the proper technique, Think Pair Share. Increasing student activity as a learning center needs to be improved. This study aims to improve students' mastery of English vocabulary and provide appropriate techniques for vocabulary learning. There were 2 cycles carried out, with the results of the first cycle, the class average being 60 and increasing in the second cycle to 71.15, which had reached the success criteria. Apart from the results of the score, students experienced a change in attitude to be more active and focused in analysis.